KONSEP URANG SABANA URANG DALAM PEPATAH ADAT MINANGKABAU - Mustansyir, Rizal; Munir, Misnal (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2009)
AbstractAccording to Wilhelm Diltheyâ€™s hermeneutic perspective,there are six points in reinterpreting the Minangkabauâ€™s traditional aphorism â€œUrang sabana urangâ€. First, understanding of Minangkabauâ€™s way of life is a general process, included in an ordinary life which is expressed in the aphorism. Second, theexpression of the aphorism is called â€œausdruckâ€, Minangkabauâ€™sexpression of life experiment and historicity. Third, humancharacteristics in Minangkabauâ€™s aphorism consist of: â€œurang,urang-urang, tampan urang, angkuh-angkuh urang, urangurangan, urang sabana urangâ€. Fourth, â€œurang sabana urangâ€ is a man who has excellent characteristics. Fifth, the globalization influence and the modern culture have changed Minangkabauâ€™s insight of â€œurang sabana urangâ€ concept so that it needs a reinterpretation in order to be understood by youth of Minang. Sixth, the epistemological dimension in Minangkabauâ€™s aphorism synthesizes an empirical aspect and rationality. The metaphysical dimension of the aphorism shows a relation between tradition and religion so that it arise the principle of â€œadat basandi syarak, syarak basandi kitabullahâ€. The axiological dimension in the aphorism is seen as a criterion of values which is an obligation for Minangs to prevent their identity asâ€ urang sabana urangâ€.Keyword: urang sabana urang, adat basandi syarak, syarakbasandi kitabullah, Minangkabau custom aphorism.